The Roles of the Gut Microbiota and Chronic Low-Grade Inflammation in Older Adults With Frailty - Xu, YuShuang; Liu, XiangJie; Liu, XiaoXia; Chen, Di; Wang, MengMeng; Jiang, Xin; Xiong, ZhiFan (Frontiers in Cellular and Infection Microbiology, 2021)
Frailty is a major public issue that affects the physical health and quality of life of older adults, especially as the population ages. Chronic low-grade inflammation has been speculated to accelerate the aging process as well as the development of age-related diseases such as frailty. Intestinal homeostasis plays a crucial role in healthy aging. The interaction between the microbiome and the host regulates the inflammatory response. Emerging evidence indicates that in older adults with frailty, the diversity and composition structure of gut microbiota are altered. Age-associated changes in gut microbiota composition and in their metabolites contribute to increased gut permeability and imbalances in immune function. In this review, we aim to: identify gut microbiota changes in the aging and frail populations; summarize the role of chronic low-grade inflammation in the development of frailty; and outline how gut microbiota may be related to the pathogenesis of frailty, more specifically, in the regulation of gut-derived chronic inflammation. Although additional research is needed, the regulation of gut microbiota may represent a safe, easy, and inexpensive intervention to counteract the chronic inflammation leading to frailty.